PEMBIARAN PUNGUTAN PARKIR DI KAWASAN SIMPANG LIMA (STUDI TENTANG: KETIDAKPATUHAN TERHADAP KEBIJAKAN TARIF RETRIBUSI PARKIR) - Muhammad Fadhil Anshori; wahid Abdulrahman (Journal of Politic and Government Studies, 2026)
This research is motivated by the phenomenon of parking attendants' non compliance with the parking fee policy in the Simpang Lima area of Semarang City, which has led to illegal parking levies and leakage of Regional Original Revenue (PAD). Although the tariff regulation is stipulated in Mayoral Regulation Number 37 of 2021, the practice of charging fees above the official limit is still frequently found in the field. The purpose of this study is to analyze the implementation of the parking fee policy, identify the factors causing parking attendant non compliance, and evaluate the role of the Semarang City Government in overseeing the area. The method used is qualitative with a descriptive approach, where data was collected through in-depth interviews with regulators (the Transportation Agency), field implementers (parking attendants), and service users. The results indicate that policy implementation is hampered by weak communication, limited supervisory resources, and excessive discretion by parking attendants who exploit the momentum of certain events to unilaterally raise fees. Furthermore, the limited availability of official parking spaces forces the public to adopt a permissive attitude towards illegal parking fees. The conclusion of this study is that parking attendant non-compliance is rooted in structural failures of the street-level bureaucracy and a lack of firm sanctions, necessitating strengthened oversight and the provision of more adequate parking spaces. This study recommends improving governance through digitizing the payment system and more responsive oversight to curb illegal parking charges.